Anatomy and Development of the Mammalian External Auditory Canal: Implications for Understanding Canal Disease and Deformity - Mozaffari, Mona; Nash, Robert; Tucker, Abigail S. (Frontiers in Cell and Developmental Biology, 2021)
The mammalian ear is made up of three parts (the outer, middle and inner ear), which work together to transmit soundwaves into neuronal signals perceived by our auditory cortex as sound. This review focuses on the often-neglected outer ear, specifically the external auditory meatus (EAM), or ear canal. Within our complex hearing pathway, the ear canal is responsible for funnelling soundwaves toward the tympanic membrane and into the middle ear, and as such is a physical link between the ear drum and the outside world. Unique anatomical adaptations, such as its migrating epithelium and cerumen glands, equip the ear canal for its function as both a conduit and a cul-de-sac. Defects in development, or later blockages in the canal, lead to congenital or acquired conductive hearing loss. Recent studies have built on decades-old knowledge of ear canal development and suggest a novel multi-stage, complex and integrated system of development, helping to explain the mechanisms underlying congenital canal atresia and stenosis. Here we review our current understanding of ear canal development; how this biological lumen is made; what determines its location; and how its structure is maintained throughout life. Together this knowledge allows clinical questions to be approached from a developmental biology perspective.